Complexity: The Emerging Science at the Edge of Order and Chaos - Waldrop, Mitchell M. (Touchstone Press)
In a rented convent in Santa Fe, a revolution has been brewing. The ac tivists are not anarchists, but rather Nobel Laureates in physics and economics such as Murray Gell-Mann and Kenneth Arrow, and pony-tailed graduate students, mathematicians, and computer scientists down from L os Alamos. They've formed an iconoclastic think tank called the Santa Fe Institute, and their radical idea is to create a new science called complexity. These mavericks from academe share a deep impatience with the kind of linear, reductionist thinking that has dominated science since the time of Newton. Instead, they are gathering novel ideas abou t interconnectedness, coevolution, chaos, structure, and order - and t hey're forging them into an entirely new, unified way of thinking abou t nature, human social behavior, life, and the universe itself. They w ant to know how a primordial soup of simple molecules managed to turn itself into the first living cell - and what the origin of life some f our billion years ago can tell us about the process of technological i nnovation today. They want to know why ancient ecosystems often remain ed stable for millions of years, only to vanish in a geological instan t - and what such events have to do with the sudden collapse of Soviet communism in the late 1980s. They want to know why the economy can be have in unpredictable ways that economists can't explain - and how the random process of Darwinian natural selection managed to produce such wonderfully intricate structures as the eye and the kidney. Above all , they want to know how the universe manages to bring forth complex st ructures such as galaxies, stars, planets, bacteria, plants, animals, and brains. There are commonthreads in all of these queries, and these Santa Fe scientists seek to understand them. Complexity is their stor y: the messy, funny, human story of how science really happens. Here i s the tale of Brian Arthur, the Belfast-born economist who stubbornly pushed his theories of economic ch